The Communication Culture of Mosque Caretakers in Maintaining Congregational Harmony in Urban Housing - Mauludi; Reka Gunawan; Moh. Hamim Assidik; Dian Adi Perdana; Asri Astria (Mimbar Agama Budaya, 2026)
The study investigates the egalitarian-transformative communication of mosque managers across varied metropolitan contexts to sustain congregational unity. The study is prompted by disputes among congregations from different Islamic traditions, especially the Nahdlatul Ulama, Muhammadiyah, and Salafi organizations, in which differences in ritual preferences may underpin opposing claims to mosque identity. Data was collected through a qualitative case study approach, employing in-depth interviews, observations, and document analysis. The results show that harmony is not maintained through standardized religious practices, but through recognition of differences, creation of dialogical spaces, equitable distribution of religious roles, and informal daily communication. Mosque leadership is not just an administrative authority but also a cultural mediator, negotiating symbols, mitigating potential disputes, and fostering congregational interaction. Egalitarian-transformative communication is presented as a methodology for managing intra-Muslim difference and improving social cohesion in metropolitan mosque communities.